Epidemiological and clinical features of hump-nosed pit viper (Hypnale hypnale and Hypnale zara) envenoming in children. - R M M K Namal Rathnayaka; P E Anusha Nishanthi Ranathunga; S A M Kularatne (Public Library of Science (PLoS), 2022)
Background Bites by the hump-nosed pit vipers (HNPV) of the genus Hypnale are the commonest type of venomous snakebites in Sri Lanka. Their bites frequently cause local effects while rarely causing systemic envenoming, that may include acute kidney injury and coagulopathy. There are 3 species of genus Hypnale including H. hypnale, H. zara and H. nepa from which latter two are endemic to Sri Lanka. Virtually all studies on HNPV bites in Sri Lanka are focused on adults except two studies in paediatric group. The aims of this study were to describe the epidemiology and clinical manifestations of HNPV bites in a group of children admitted to a tertiary care hospital in Sri Lanka. Methodology/principal findings This was a prospective observational study carried out in Teaching Hospital Ratnapura, Sri Lanka over 27 months commencing from May 2020 including all children aged up to 14 years with the history of HNPV bites. There were 40 (56%) HNPV bites, of them 28 (70%) were males. The age was 84 months (50.2-120 months). Majority (n = 21;52.5%) were bitten during day-time (06:00-17:59) in home gardens (n = 20; 50%) on lower limbs (n = 24;60%). Most children (n = 30;75%) were admitted to the medical facility < 4 hours after the snakebite [90 min (40-210 min)] and the hospital stay was 4 days (3-5 days). Local envenoming was observed in 38 patients (95%) and systemic effects developed in 4 patients (10%) as mild coagulopathy. Local effects include local pain (n = 30; 94%), swelling (n = 38;95%), blistering (n = 11;27.5%), necrosis at the site of bite (n = 11; 27.5%), regional lymph node enlargement (n = 8;20%) and local bleeding (n = 4;10%). For the local effects, surgical interventions were needed in 10 children (25%) and 3 (7.5%) of them developed acute compartment syndrome leading to fasciotomy. Leucocytosis (n = 28;78%) and eosinophilia (n = 9;27%) were the prominent laboratory findings. All got recovered except in patients with fasciotomy who got permanent scar. Conclusions/significance Hump-nosed pit viper bites mostly cause local effects and rarely systemic envenoming in children. Compartment syndrome is common in children following their bites.